Logistics of recycling and the procedure of marketing communication explanation of energy saving with the use of alternative energy sources - Kasian, S. (Видавництво Львівської політехніки, 2016)
This paper is devoted to the enhancement of theoretical, methodological provisions and practical scientific approaches to the organization of logistics of recycling and forming of the procedure of a marketing communication explanation of importance of energy saving with the use of alternative energy sources. In the article compared approaches of scientists and practices in the sphere of marketing concerning of energy efficient development due to the corresponding integrated marketing communication and logistic providing. Determined features of marketing communication ensuring process of waste distribution and the organization of logistics of recycling on the industrial and service enterprises. In the article determined the semantic principles of marketing communication explanation of energy saving in industrial and household spheres and developed the procedure of marketing communication explanation for the enterprises and physical persons of importance of energy saving with the use of alternative energy sources, ecologically safe housekeeping of economic agents in Ukraine. In this scientific research characterized application of marketing and logistics in the sphere of implementation of innovative energy-saving technologies at the national level, in work of local government departments, industrial enterprises and housing and municipal sector, in Ukraine and the world. Удосконалено теоретико-методологічні положення і практичні наукові підходи до організації логістики рециклінгу та формування процедури комунікаційного роз’яснення важливості енергозаощадження з використанням альтернативних джерел енергії. Порівняно підходи науковців і практиків у сфері маркетингу щодо енергоефективного розвитку за рахунок відповідного інтегрального маркетингового комунікаційного і логістичного забезпечення. Окреслено особливості маркетингового комунікаційного забезпечення щодо розподілення відходів та організації логістики рециклінгу на промислових і сервісних підприємствах. Визначено змістові засади маркетингового комунікаційного роз’яснення енергозбереження у промисловій та побутовій сферах та розроблено процедуру маркетингового комунікаційного роз’яснення для підприємств та фізичних осіб важливості енергозаощадження з використанням альтернативних джерел енергії, екологічно безпечного господарювання економічних агентів в Україні. У цьому науковому дослідженні охарактеризовано застосування маркетингу і логістики в сфері впровадження інноваційних енергозбережних технологій на державному рівні, у роботі органів місцевого самоврядування, промислових підприємств та житлово-комунального сектору в Україні та світі.
Логістика рециклінгу і процедура маркетингового комунікаційного роз’яснення енергозаощадження з використанням альтернативних джерел енергії
Keywords: logistics of recycling; procedure; integrated marketing communication; energy saving; logistic providing; логістика рециклінгу; процедура; інтегровані маркетингові комунікації; енергозаощадження; логістичне забезпечення